1991
DOI: 10.1007/bf01741328
|View full text |Cite
|
Sign up to set email alerts
|

In vitro immunomodulating effect of protein-bound polysaccharide, PSK on peripheral blood, regional nodes, and spleen lymphocytes in patients with gastric cancer

Abstract: PSK, a protein-bound polysaccharide, has been widely used for cancer immunotherapy in Japan. However, the mechanism of its immunomodulatory effect has not been fully clarified. In the present study the in vitro effect of PSK on the lymphocytes of patients with gastric cancer was studied. Culturing lymphocytes with PSK at 5-100 micrograms/ml increased the level of DNA synthesis, and augmented the cytotoxicities against K562 and KATO-3. Flow-cytometric analysis also showed an increase in the proportion of interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Based on some experimental findings, it appears that an immune modulating effect should be considered even for mAbs used in aGC treatment. [80][81][82][83][84][85][86] Interestingly, in aGC, while bevacizumab did not demonstrate a significant benefit, indeed, in our analysis, we observed that trials evaluating other agents showed a highly significant efficacy in term of survival benefit in the anti-angiogenesis subgroup in aGC. 17,35,37 Several studies suggested that targeting VEGFR2 may elicit and improve the immune response directed toward the tumor and its microenvironment trough different mechanisms including direct activation of CD8 C cells and targeting of the FOXP3 high regulatory T cells.…”
Section: Discussionsupporting
confidence: 48%
“…Based on some experimental findings, it appears that an immune modulating effect should be considered even for mAbs used in aGC treatment. [80][81][82][83][84][85][86] Interestingly, in aGC, while bevacizumab did not demonstrate a significant benefit, indeed, in our analysis, we observed that trials evaluating other agents showed a highly significant efficacy in term of survival benefit in the anti-angiogenesis subgroup in aGC. 17,35,37 Several studies suggested that targeting VEGFR2 may elicit and improve the immune response directed toward the tumor and its microenvironment trough different mechanisms including direct activation of CD8 C cells and targeting of the FOXP3 high regulatory T cells.…”
Section: Discussionsupporting
confidence: 48%
“…Increased numbers of immunologically competent cells and a rise in dendritic and Tc cells capacity of tumor infiltrate were noted in patients who received PSK. Krestin affects the phenotypic and functional maturation of dendritic cells from human CD14+ cells [61], and stimulates the phagocytic activity of macrophages [41]. In addition, it stimulates expression of TNF-α, IL-1, IL-6, and IL-8 [62–65].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In vitro studies have confirmed that PSK induces the expression of several cytokine genes including TNF-α, IL-1, IL-1R, IL-2, IL-4, IL-6, IL-7, and IL-8 [12][13][14][15] . Anti-neoplastic effects of PSK have also been reported in animal models, and involve the radical trapping and modulation of cytokine production and effector cell functions [16,17] .…”
Section: Introductionmentioning
confidence: 99%